Monolingual Instruction in Multi-lingual Classrooms at Primary Level in Nepal - Timsina, Lok Nath (ILAM इलम, 2024)
This article attempts to explore the classroom activities conducted by using monolingual instruction in multilingual classrooms. The main objective of this article is to explore the difficulties faced by both teachers and students because of the medium of classroom instruction where the students come from different linguistic backgrounds. The primary data were collected from three teachers who have been teaching in basic level for more than five years. The research suites were three community schools located in Madhyapur Thimi Municipality, Bhaktapur. Class observation, in-depth interviews and informal conversation with the teacher participants were the tools for data collection. From the data collected through these tools and study of the available literature, it was found that teachers feel difficulties in delivering sufficient information and the students feel problems in grasping enough ideas from their non-native language used as the medium of instruction in multilingual classroom setting. Uses of students’ mother tongues, formation of mixed linguistic groups, presenting plenty of teaching materials and conducting sufficient interaction between teachers and students and among the students both inside and outside the classroom were helpful to minimize such difficulties in teaching.